2021
DOI: 10.48550/arxiv.2111.11761
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Confronting quantum-corrected teleparallel cosmology with observations

Reginald Christian Bernardo,
Che-Yu Chen,
Jackson Levi Said
et al.

Abstract: It has been shown that at the semi-classical order, gravitational theories with quantum fluctuations can be effectively recast as modified theories of gravity with non-minimal gravity-matter couplings. We proceed from an observational perspective and see whether such quantum fluctuations can leave imprints on the late Universe. Within the teleparallel formulation, we investigate a representative model in this general class of modified gravitational theories inlaid with quantum fluctuations, and determine the c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Further, for that extended theory, the process of quantum fluctuations induced by matter-gravity couplings were studied [325]. Further, it was found that these fluctuations are compatible with cosmological observations [326].…”
Section: Theories Non-minimally Coupled With Mattermentioning
confidence: 67%
“…Further, for that extended theory, the process of quantum fluctuations induced by matter-gravity couplings were studied [325]. Further, it was found that these fluctuations are compatible with cosmological observations [326].…”
Section: Theories Non-minimally Coupled With Mattermentioning
confidence: 67%